Transurethral resection of the prostate stricture management - Jian-Wei Wang; Li-Bo Man (Asian Journal of Andrology, 2020)
For more than nine decades, transurethral resection of the prostate remains the gold standard for the surgical treatment of lower urinary tract symptoms due to benign prostatic obstruction. The occurrence of urethral strictures after transurethral resection of the prostate is one of the major late complications and has been reported as the leading cause of iatrogenic urethral strictures in patients older than 45 years who underwent urethroplasty. Although several postulations have been proposed to explain the urethral stricture after transurethral resection of the prostate, the exact etiology of urethral stricture after TURP is still controversial. Suggested etiological factors of urethral stricture formation after transurethral resection of the prostate include infection, mechanical trauma, prolonged indwelling catheter time, use of local anesthesia, and electrical injury by a stray current. One single treatment option is not appropriate for all stricture types. The management of urethral stricture following transurethral resection of the prostate includes minimally invasive endoscopic methods, including urethral dilation and direct visual incision, or open surgical procedures with varying urethroplasty techniques. Although scientific studies focusing on urethral strictures after transurethral resection of the prostate are relatively limited and sparse, we can apply the principles of urethral stricture management before making decisions on individual stricture treatment.